HUBUNGAN ANTARA DERAJAT OBSTRUKSI SALURAN NAFAS SERANGAN AKUT ASMA DENGAN JUMLAH SEL-SEL INFLAMASI DARAH TEPI - Kusuma, HMS. Chandra; Kalim, Kusworini Handono; Muid, Masdar (Jurnal Kedokteran Brawijaya, 2004)
There now exists compelling evidence of a role for  cell-mediated immunity in the pathogenesis of asthma, but little information is available as to what extent this process participates in the disease severity. The hypothesized of this reseach that the severity of acute asthma exacerbation in children is associatedwith the activation of T-lymphocytes whose products regulate, at least in part, the mobilization and recruitment of eosinophyls and thereby disease severity. The aims of this research, therefore, were to compare the peripheral blood T-lymphocytes from acute asthmaticand no asthmatic normal control children matched for age and sex, and to attempt to correlate the percentages of T-lymphocytes in the asthmatic with the numbers of peripheral  blood eosinophyls and with disease severity. Fifty one children with acute asthma exacerbation were compared with thirty one no asthmatic, normal children matched for age and sex. Peripheral blood CD4+ and  CD8+ T-lymphocytes was measured using immuno histochemical staining. Peripheral blood eosinophils were measured using anautomated laser cytometer. Asthma exacerbation severity was assessed by a symptom score and spirometri. The absolute numbers  of eosinophils and CD4+ T-lymphocytes of the asthmatic were elevated as compared to the non-asthmatic normal control, whereas the numbers of CD8+ T-lymphocyte decreased significantly.